2022
DOI: 10.3390/nano12030419
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Enhancement in Parabolic through Solar Receiver: A Three-Dimensional Numerical Investigation

Abstract: Parabolic trough collectors (PTC) are one of the most established solar concentrating systems which have been used in a wide variety of applications. Enhancing their performance is critical to establish them as a viable technology. Internal obstacles are an intriguing way for improving the collector’s performance. However, the usage of obstacles results in increasing pressure loss. The purpose of this research is to numerically explore the impact of introducing obstacles to the receiver tube of a parabolic tro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Due to their remarkable heat transfer characteristics, researchers have explored various types of nanofluids extensively to gain a deeper understanding of their behavior. [1][2][3][4][5][6][7][8][9][10][11] Dealing with problems related to this foundational fluid is deemed a formidable task, primarily owing to the presence of nonlinear equations. The introduction of similarity invariants plays a pivotal role in diminishing the count of independent variables within the resulting equations for such problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to their remarkable heat transfer characteristics, researchers have explored various types of nanofluids extensively to gain a deeper understanding of their behavior. [1][2][3][4][5][6][7][8][9][10][11] Dealing with problems related to this foundational fluid is deemed a formidable task, primarily owing to the presence of nonlinear equations. The introduction of similarity invariants plays a pivotal role in diminishing the count of independent variables within the resulting equations for such problems.…”
Section: Introductionmentioning
confidence: 99%
“…The term “nanofluid” refers to a mixture where nanometer‐sized nanoparticles are dispersed within traditional base fluids, forming a continuous phase. Due to their remarkable heat transfer characteristics, researchers have explored various types of nanofluids extensively to gain a deeper understanding of their behavior 1–11 . Dealing with problems related to this foundational fluid is deemed a formidable task, primarily owing to the presence of nonlinear equations.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the nanotechnology field has significantly strengthened its position in many branches of human activity [ 1 , 2 , 3 , 4 , 5 , 6 ]. The design, development, and study of nanostructures attract the great attention of scientists all around the world because of the wide range of nanoparticle applications.…”
Section: Introductionmentioning
confidence: 99%
“…By keeping the above applications in view, Ghasemi et al 1 proposed an Eulerian two-phase method to examine the improved heat transmission in PTSC by considering nanoliquid motion through it. A case study investigating the practical usage of solar energy in PTSC considering the Maxwell model was hypothetically premeditated by Jamshed et al 2 Later on, Fahim et al 3 protracted the work for a three-dimensional nano case and concluded that the heat transmission rate could be improved by enhancing the nanoparticle concentration. The effect of mass diffusion on hydrodynamic 3D Mawell nanoliquid motion above an elongated superficial in the incidence of cross-diffusion properties was exactly examined by Reddy and Lakshminarayana.…”
Section: Introductionmentioning
confidence: 99%